2021
DOI: 10.1111/ene.15058
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light chain as a surrogate of cognitive decline in sporadic and familial frontotemporal dementia

Abstract: Background and purpose: Neurofilament light chain (NfL) has recently been proposed as a promising biomarker in frontotemporal dementia (FTD). We investigated the correlation of both cerebrospinal fluid (CSF) and serum NfL with detailed neuropsychological data and cognitive decline in a cohort of sporadic and familial FTD. Methods: CSF and serum NfL, as well as conventional CSF Alzheimer's disease (AD) biomarkers (Aβ42, t-Tau, p-Tau181), were determined in 63 FTD patients (30 sporadic-FTD, 20 with progranulin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…These analytes could represent measures of the neuropathological AD features, where blood‐derived GFAP and p‐Tau181 are measures of Aβ burden [10, 18, 35], p‐Tau181 also of tauopathy [10, 17], and NfL of neurodegeneration [8, 17, 30, 35], similar to the scheme of the ATN classification for CSF. Therefore, under some circumstances, they could act as surrogates for the ATN scheme through a less invasive and less expensive method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These analytes could represent measures of the neuropathological AD features, where blood‐derived GFAP and p‐Tau181 are measures of Aβ burden [10, 18, 35], p‐Tau181 also of tauopathy [10, 17], and NfL of neurodegeneration [8, 17, 30, 35], similar to the scheme of the ATN classification for CSF. Therefore, under some circumstances, they could act as surrogates for the ATN scheme through a less invasive and less expensive method.…”
Section: Discussionmentioning
confidence: 99%
“…have allowed for the reliable quantification of the CSF core AD proteins in peripheral blood, potentially reducing the need for a lumbar puncture during monitoring and/or screening of patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Brain imaging and several biofluid proteins have been proposed as biomarkers for both ALS and FTD (Al Shweiki et al , 2019; Ashton et al , 2021; Bellini et al , 2022; Benussi et al , 2019; Bian et al , 2008; Borroni et al , 2015; Bourbouli et al , 2017; Bright et al , 2019; Chouliaras et al , 2022; Das et al , 2022; Delaby et al , 2020; Eratne et al , 2022; Feneberg et al , 2018; Forgrave et al , 2019; Goncalves et al , 2017; Gonzalez-Garza et al , 2018; Hansson et al , 2019; Hu et al , 2013; Jiskoot et al , 2019; Katisko et al , 2021; Katisko et al , 2020; Krishnan et al , 2022; McCarthy et al , 2018; Meeter et al , 2017; Meeter et al , 2018; Niikado et al , 2019; Oeckl et al , 2022; Prado et al , 2018; Rossi et al , 2018; Sheikh-Bahaei et al , 2017; Silva-Spinola et al , 2022; Teunissen et al , 2016; Thijssen et al , 2022; Turner et al , 2009; van der Ende et al , 2020; Verde et al , 2021; Wilson et al , 2022; Xu et al , 2016). Among the proteins, noticeable are neurofilament light chain (NfL), TDP-43 and, phospho-tau, amyloid beta and glial fibrillary acidic protein (GFAP).…”
Section: Introductionmentioning
confidence: 99%
“…After an axonal injury or neuronal degeneration, NfL is released into interstitial fluid and eventually into CSF and plasma [56,57]. NfL levels are increased in frontotemporal dementia [58], small vessel disease [59], Parkinson's disease [60] and AD [61]. The results of crosssectional studies comparing plasma NfL concentrations and cognitive performance are mixed: some studies have found associations [62], whereas others did not [63,64].…”
Section: Peripheral-blood-based Measures Of Neuropathologymentioning
confidence: 99%